PELAKSANAAN PROMOSI PENJUALAN TIKET PESAWAT DI PT. HAMKA GIAT TOUR AND TRAVEL PEKANBARU Implementation Sales Promotion Airlines Ticket in PT. Hamka Giat Tour and Travel Pekanbaru - ", Nurzanah; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study is based on the sales promotion airlines ticket activity at “ PT. Hamka Giat Tour and Travel Pekanbaru”. In marketing its companyproduct needs to haves media between consumer and company that is through promotion as the communication media between company and consumer. In order the promotion can interest the attention and influence consumer in buying, so the company does promotional mix that implies several variables those are personal selling, sales promotion, and wind of mouth. Aims to spread information, influence or persuade and remind the target market of the company and its products to be willing to accept, purchase, and loyal to the products offered by the company concerned.The sampel is this research is influential consumer about purchasing airlines ticket. In this study the authors used descriptive quantitative analysis techniques, that describe the real situation, particularly on the aspects studied, and the techniquedata collection is with questioner method and interview .The study design by means of descriptive analysis is intended to explain to describe specifically how the implementation of the sales promotion airlines ticket in PT. Hamka Giat Tour and Travel Pekanbaru in order to increase sales through promotion. The research funding indicates that can be seen PT. Hamka Giat Tour and Travel Pekanbaru is present-able, it can be seen from the reaction respondent to the promotional tools carried out by company.Key words : Sales Promotion, Implementation Promotion, Ticket Airlines,